2021
DOI: 10.1097/phm.0000000000001918
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Dextrose Prolotherapy, an Alternative to Intra-Articular Injections With Hyaluronic Acid in the Treatment of Knee Osteoarthritis

Abstract: Intra-articular injections with hyaluronic acid are recommended in the treatment of knee osteoarthritis; however, hypertonic dextrose prolotherapy has been reported as effective and safe. The aim was to evaluate the effectiveness of hypertonic dextrose prolotherapy for pain reduction and improvement of function in individuals with knee osteoarthritis in comparison with hyaluronic acid by meta-analysis. The search was performed in electronic databases. Six studies were included (395 participants). No statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…54 Clinical studies have reported the efficacy of PHD in pain control and improvement of function in KOA patients. [55][56][57] Some studies have compared PHD with IAI of CSs and reported that, in the short term, CSs are more effective in controlling pain and improving function; however, in the medium term, the result is reversed and PHD is more effective. 57 A recent meta-analysis compared the efficacy of HA injections with PHD in patients with KOA and reported equal efficacy in reducing pain and improving function at 3 months of follow-up.…”
Section: Intra-articular Injections Of Botulinum Toxinmentioning
confidence: 99%
See 4 more Smart Citations
“…54 Clinical studies have reported the efficacy of PHD in pain control and improvement of function in KOA patients. [55][56][57] Some studies have compared PHD with IAI of CSs and reported that, in the short term, CSs are more effective in controlling pain and improving function; however, in the medium term, the result is reversed and PHD is more effective. 57 A recent meta-analysis compared the efficacy of HA injections with PHD in patients with KOA and reported equal efficacy in reducing pain and improving function at 3 months of follow-up.…”
Section: Intra-articular Injections Of Botulinum Toxinmentioning
confidence: 99%
“…57 A recent meta-analysis compared the efficacy of HA injections with PHD in patients with KOA and reported equal efficacy in reducing pain and improving function at 3 months of follow-up. 55 Prolotherapy with hypertonic dextrose has also been compared with IAI of PRP, observing no differences between the 2 interventions in pain reduction at 6 months of follow-up. 56 Prolotherapy with hypertonic dextrose has been reported to be a safe intervention, but it is not exempt from minor adverse reactions such as pain, swelling, and stiffness.…”
Section: Intra-articular Injections Of Botulinum Toxinmentioning
confidence: 99%
See 3 more Smart Citations